The Role of Permanent Learning and Human Capital in the Sector of Tourism - Simándi, Szilvia (Turizam, 2018)
Human capital is a key factor in the development of sustainable tourism. In the sector of tourism, the quality of the provided services receives an important role: the permanent learning and the continuous renewal accompany the development of touristic regions. When examining lifelong learning, the focus of the research is put on experts working in tourism: providing touristic services that need living labour mostly; especially nowadays, tourism can be more and more seen as consuming experience, a service providing experience, in which human capital has a determinative significance. An online questionnaire survey was carried out in the framework of a regional research, among accommodation providers, in the framework of a random sampling (n=376). In this survey, learning in non-formal environment was put into focus. Special attention was paid to autonomous learning and learning initiated by the individuals. The questioned experts of tourism can be categorized from the points of view of getting into the sector and the continuous (lifelong) learning. In connection with the practical implementation of lifelong learning and professional development, a structured range of proposals confirmed with examples were also compiled from the answers about learning.